Monitoring the solid-state dewetting of densely packed arrays of Au nanoparticles. (May 2019) - Magnozzi, M; Ferrera, M; Canepa, M; Bisio, F
Abstract: We report a real time, in-situ spectroscopic ellipsometry study of the temperature-induced solid-state dewetting of Au nanowires into nanoparticles. Very large spectral variations are observed at different temperatures. Analysis of the key features in the acquired spectra reveals two different regimes: up to 300 °C the variation in the optical response is dominated by solid-state dewetting, while above that temperature, smaller variations not compatible with such mechanism are visible. Therefore our ellipsometry measurements allow us to determine in real time at which temperature the solid-state dewetting ceases and the morphology of our sample becomes stable. We point out that this observation is possible thanks to the higher sensitiviy of ellipsometry with respect to reflectance/transmittance measurements.